2013
DOI: 10.1007/s10534-013-9689-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined chelation of lead (II) by deferasirox and deferiprone in rats as biological model

Abstract: In order to investigate the capability of two chelators deferasirox (DFX or ICL670) and deferiprone (L1) in removing lead from the body, the present research was performed. Two does levels of 40 and 80 mg/kg body weight of lead (II) chloride was given to rats as biological model for 45 days. After 45 days, some toxicity symptoms were observed in rats such as loss of hair and weight, appearance of red dots around eyes, weakness and irritability. After lead application, chelation therapy with DFX and L1 as mono … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The results clearly confirmed the tridentate (O,N,O) coordination of the ligand in all cases, the very high stability of the iron-L B 3À complexes, the high selectivity of H 3 L B for iron in the presence of the studied other biometals, and the possibility of sequestration of aluminium(III) by H 3 L B as well [7,8]. A biological study also supported the applicability of H 3 L B (first of all in combination with HDFP) for the removal of toxic lead(II) from the body [10]. Quantitative evaluation of the effects of iron(III) chelation on the physiological concentrations of essential metal ions like copper(II) and zinc(II) showed that these metal ions do not disturb iron(III) chelation by H 3 L B [11].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results clearly confirmed the tridentate (O,N,O) coordination of the ligand in all cases, the very high stability of the iron-L B 3À complexes, the high selectivity of H 3 L B for iron in the presence of the studied other biometals, and the possibility of sequestration of aluminium(III) by H 3 L B as well [7,8]. A biological study also supported the applicability of H 3 L B (first of all in combination with HDFP) for the removal of toxic lead(II) from the body [10]. Quantitative evaluation of the effects of iron(III) chelation on the physiological concentrations of essential metal ions like copper(II) and zinc(II) showed that these metal ions do not disturb iron(III) chelation by H 3 L B [11].…”
Section: Introductionsupporting
confidence: 52%
“…The direct correlation between the very effective iron-binding behaviour of H 3 L B and its above-mentioned importance in the treatment of iron overload diseases initiated studies in several laboratories regarding its metal complexation [7][8][9][10]. In addition to iron, some other biorelevant metal ions (Ca(II), Mg(II), Cu(II) and Zn(II)), the toxic Al(III) and also V(IV)) were involved in solid state, solution equilibrium and redox activity studies with H 3 L B and some derivatives by Hegetschweiler et al [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether thallium interferes with iron absorption and/or its subsequent metabolism, but this could take place along pathways for essential metals ( 22 ). If this is the case, iron deficiency could result in increased absorption, as is observed for several inorganic elements such as manganese, cobalt, lead, cadmium, gallium, and indium ( 23 , 24 ). Therefore, thallium seems to interfere with the iron uptake and transfer mechanism.…”
Section: Discussionmentioning
confidence: 98%